BAURAN PEMASARAN PADA USAHA RUMAH ES â€œBOâ€ MOKUPA DI DESA MOKUPA KECAMATAN TOMBARIRI KABUPATEN MINAHASA - Kathleen R. Sondakh; Lyndon R.J. Pangemanan; Celcius Talumingan; Gene H.M. Kapantow (Universitas Sam Ratulangi, 2015)
ABSTRACTÂ The changes development of the knowledge society in the culinary world makes some people who have to be fond of the consumption a variety foods race each other to create a new type of food, tasty and contains nutrients that can be introduced in the world business and can be change society consumption pattern. Business of the culinary is a business opportunity that will never die as long as people still need food for eat, and of course, humans need food for survival futhermore. Another factors reason is due to the amount of business opportunities promising society have Manado city to obtain the benefits of the culinary business. Ice house